Magneto Electrical: Sumber Energi Masa Depan - Zuhdiana Ulil Albab; Dhea Novalia Pratiwi; Syafarotun Nur Laili; Azra Hafiza; Ahmad Jahrudin (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2021)
In a highly developed era, of course, it will require the use of electricity to continue to increase, and the problem is to meet the high electricity demand, on the other hand the construction of electricity infrastructure that takes a long time will hamper the supply of electricity, therefore renewable energy sources are needed to overcome this problem. that's why we tried to make Magneto Electrical. Magneto Electrical is a Future Energy Source created to provide a safe, efficient, and environmentally friendly source of electrical energy. The purpose of this research is to design and manufacture Magneto Electrical: Future Energy Sources. The research method used is research and development (R&D). This research method is used to research so that it can produce new products and then test their effectiveness. Magneto Electrical works based on Faraday's Law, namely when a conductor is rotated in a magnetic field so that it cuts the magnetic lines at the end of the conductor, an emf (line of electric force) will be generated. Through this research, researchers have succeeded in designing and making Magneto Electrical: Future Electrical Energy Sources. By utilizing the repulsion between magnets so that motion energy is produced which is then converted into electrical energy. From the tests that have been carried out, it was found that the tool made is capable of producing 15 Volts of electrical energy.